POTENSI BAHAYA BAGI KESELAMATAN PENGUNJUNG DI KAWASAN WISATA PANTAI PANGANDARAN KABUPATEN PANGANDARAN JAWA BARAT - EKS Harini Muntasib; Melly Maria Ulfah; Agustinus Samosir; Resti Meilani (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Pangandaran Beach Tourism Area is one of leading tourism areas in West Java. During certain period of time, hazard has often cause accidents toward visitors in the area. Therefore, there is a need to identify physical and biological hazards which threaten visitors’ safety in order to develop visitor safety management. Research was carried out in June – July 2011, and an update was conducted in January – February 2017, which covered three locations, i.e. Pantai Barat, Pantai Timur, and Pantai Pasir Putih. Field observation, interview with visitors, community and lifeguard, and literature review were employed in data collection. A hundred respondents for each visitor and community was selected using convenient sampling method. The result found rip current, plunging wave, tsunami, earthquake, wave, and tide as physical hazard, while jellyfish, sea snake, sea urchin, lionfish, and stone fish as biological hazard found in the sea, and long-tailed macaque as terrestrial biological hazard. Rip current possessed substantial risk that had to be avoided through the establishment of swimming prohibition area. Visitor’s safety management technique option for rip current hazard involved a socialization toward visitors about self-rescue technique in case they are swept by rip current.